(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
This study evaluated the diagnostic efficacy of two methods for detecting Banana Bunchy Top Virus (BBTV) in abaca: conventional Polymerase Chain Reaction (PCR) and a novel colorimetric Loop-Mediated Isothermal Amplification (LAMP) assay. The study’s purpose was to determine which method is more effective for field-based surveillance in the Philippines, a country with significant economic reliance on abaca production. A total of 243 leaf samples from key abaca-producing municipalities in the Caraga Region were collected and tested.The LAMP assay exhibited a significantly higher detection rate, identifying 85.2% of samples as positive compared to only 35.8% by conventional PCR (χ2 = 121.92, df = 1, p < 0.001). This diagnostic superiority was consistent across all four provinces surveyed, with the most pronounced difference in Surigao del Norte, where LAMP detected 86.04% of infections compared to a mere 2.33% by PCR. These findings reveal a substantial, previously hidden, reservoir of asymptomatic and low-titer BBTV infections that evade detection by traditional methods.The novelty of this study lies in its demonstration that LAMP is not only more sensitive but also uniquely suited for resource-limited settings due to its simple visual readout and lack of reliance on complex laboratory equipment. The results highlight that relying solely on symptom-based surveillance severely underestimates the true disease prevalence. The study concludes that adopting LAMP as a cornerstone of national surveillance efforts could provide a critical advantage in curbing the silent spread of BBTV, ensuring the sustainability of the abaca industry in the Philippines.